Diabetic retinopathy in a remote Indigenous primary healthcare population: a Central Australian diabetic retinopathy screening study in the Telehealth Eye and Associated Medical Services Network project - Brazionis, L.; Jenkins, A.; Keech, A.; Ryan, C.; Brown, A.; Boffa, John; Bursell, S. (Wiley-Blackwell Publishing Ltd., 2018)
Aim: To determine diabetic retinopathy prevalence and severity among remote Indigenous Australians. Methods: A cross-sectional diabetic retinopathy screening study of Indigenous adults with Type 2 diabetes was conducted by locally trained non-ophthalmic retinal imagers in a remote Aboriginal community-controlled primary healthcare clinic in Central Australia and certified non-ophthalmic graders in a retinal grading centre in Melbourne, Australia. The main outcome measure was prevalence of any diabetic retinopathy and sight-threatening diabetic retinopathy. Results: Among 301 participants (33% male), gradable image rates were 78.7% (n = 237) for diabetic retinopathy and 83.1% (n = 250) for diabetic macular oedema, and 77.7% (n = 234) were gradable for both diabetic retinopathy and diabetic macular oedema. For the gradable subset, the median (range) age was 48 (19–86) years and known diabetes duration 9.0 (0–24) years. The prevalence of diabetic retinopathy was 47% (n = 110) and for diabetic macular oedema it was 14.4% (n = 36). In the fully gradable imaging studies, sight-threatening diabetic retinopathy prevalence was 16.2% (n = 38): 14.1% (n = 33) for clinically significant macular oedema, 1.3% (n = 3) for proliferative diabetic retinopathy and 0.9% (n = 2) for both. Sight-threatening diabetic retinopathy had been treated in 78% of detected cases. Conclusions: A novel telemedicine diabetic retinopathy screening service detected a higher prevalence of ‘any’ diabetic retinopathy and sight-threatening diabetic retinopathy in a remote primary care setting than reported in earlier surveys among Indigenous and non-Indigenous populations. Whether the observed high prevalence of diabetic retinopathy was attributable to greater detection, increasing diabetic retinopathy prevalence, local factors, or a combination of these requires further investigation and, potentially, specific primary care guidelines for diabetic retinopathy management in remote Australia. Clinical Trials registration number: Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN 12616000370404.